Speech intelligibility prediction model in room with reflective dome - Harun, Mokhtar (2005)
This thesis presents research works on developing the objective speech intelligibility prediction models in room with dome in terms of acoustics, and room and dome geometry. The purpose of the research was to enable one to predict speech intelligibility (SI) in room with dome as early as at the conceptual design stage. The developed SI prediction models have made possible the estimation of the acceptable room and dome dimension ratios for speech, the determination of the significant acoustics parameters that affect SI, and the determination of achievable SI scores at any audience area in room with dome. The research was begun with pilot study and room investigations in large mosques with dome in Johor. Similar works were later extended in Negeri Sembilan, Selangor and Kedah. Basic dimensions of room and dome, types of dome, types of ceiling, and types of material and finishes in room and on dome surfaces were obtained. Having completed room investigation activity, acoustics measurements were conducted in thirty-two mosques with dome, with dome volume ranging from 100 m3 to 10000 m3 to determine Speech Interference Level (SIL), reverberation time (RT60) and speech intelligibility assessor, Speech Transmission Index (STI); the parameters that are required for the development of SI prediction models. It was found that RT60 is able to predict minimum SI scores in area 6Â° outside sound source coverage area, which is STIOUT6(min). Average SI under dome area, STIDA(mean) is found to be efficiently predicted by average sound absorption coefficients of the room. Both STIDS(min) and STIDS(mean) are well predicted by room and dome geometry. From the simulation works, it has been found that the developed SI prediction models have achieved acceptable prediction accuracy for the practical purposes, with multiplication of 0.2 to 2.6. Therefore, the development of SI prediction models has been successful, accurate and time effective to obtain optimum achievable SI in room with dome.